Garantias autônomas: instrumento para proteção jurídica do crédito - Guilhardi, Pedro (2017)
This paper discusses demand guarantees, a legal instrument for the protection of the credit, that has been created in the context of the internacional commerce and is an atypical contract in the brazilian legal system. It analyzes the demand guarantees from the perspective of its usage and creation in the international commerce, fractioning and isolating the legal relationships that are formed with the execution of such agreement, to allow the assessment of such legal relationships under the Brazilian legal system. Such investigation aims at avoiding that demand guarantees’ nature are detracted and, thus, it promotes the most important feature of demand guarantees, which is its immediate enforceability and security for the beneficiary, without the inconveniencies that a guarantee found on deposit of money brings with it